PENGARUH SENAM BUGAR LANSIA TERHADAP KADAR HDL DAN LDL DI BPLU MANADO - Sugeha, Stephany (e-Biomedik, 2013)
Abstract: The prevalence of decreased levels of High Density Lipoprotein (HDL) and elevated levels of Low Density Lipoprotein (LDL) in Indonesia is quite high, until increasing diseases such as stroke, dyslipidemia and Coronary Heart Disease (CHD). Gymnastic for elder is a form of exercise that moves easily followed by the elderly and can improve the health status. This study aimed to know about influence of gymnastic for elder to the levels of HDL and LDL before and after participating. This research is an experimental design with one group pre-post test. Subjects were 30 elderly people who are in Manado BPLU drawn from a population of 48 elderly people who met the inclusion criteria. Data analysis using a paired t-test with SPSS version 20.0. There are significant differences in levels of HDL (p = 0.022) and levels of LDL cholesterol (p = 0.000), before and after participating gymnastic for elder. Conclusion: Levels of HDL and LDL before and after doing SBL were significantly different. Keywords: Gymnastic for elder, HDL, LDLÂ Â  Abstrak : Prevalensi penurunan kadar High Density Lipoprotein (HDL) dan peningkatan kadar Low Density Lipoprotein (LDL) di Indonesia cukup tinggi sehingga meningkatkan penyakit seperti stroke, dislipidemia dan Penyakit Jantung Koroner (PJK). Senam bugar lansia merupakan bentuk olahraga yang gerakannya mudah diikuti oleh lansia dan dapat meningkatkan status kesehatan. Penelitian ini bertujuan untuk mengetahui pengaruh Senam Bugar Lansia terhadap kadar HDL dan LDL sebelum dan sesudah mengikuti senam bugar lansia. Penelitian ini bersifat eksperimental lapangan dengan rancangan pre-post one group test. Subjek penelitian adalah 30 lansia yang berada di BPLU Manado yang diambil dari populasi yang berjumlah 48 lansia yang memenuhi kriteria inklusi. Analisis data menggunakan t-paired test dengan program SPSS versi 20.0. Terdapat perbedaan bermakna pada kadar HDL (p=0,022) dan kadar LDL (p=0,000) sebelum dan sesudah mengikuti senam bugar lansia. Simpulan: Kadar HDL dan LDL sebelum dan sesudah melakukan senam bugar lansia berbeda secara bermakna. Kata kunci: Senam bugar lansia, HDL, LDL.